2020
DOI: 10.1186/s12934-019-1274-y
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic engineering of the antifungal, anti-MRSA auroramycin

Abstract: Using an established CRISPR-Cas mediated genome editing technique for streptomycetes, we explored the combinatorial biosynthesis potential of the auroramycin biosynthetic gene cluster in Streptomyces roseosporous. Auroramycin is a potent anti-MRSA polyene macrolactam. In addition, auroramycin has antifungal activities, which is unique among structurally similar polyene macrolactams, such as incednine and silvalactam. In this work, we employed different engineering strategies to target glycosylation and acylati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Polyene macrolactams have only been found in actinobacteria and have also shown a variety of activities (Skellam et al, 2013). In this regard, auroramycin, a polyene macrolactam, was produced by a strain of Streptomyces roseosporous with anti-MRSA and antifungal properties (Yeo et al, 2020). Additionally, Arai et al (2017) also found that an isomer of micromonolactam, isomicromonolactam, could be used as an enhancer of neural stem cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Polyene macrolactams have only been found in actinobacteria and have also shown a variety of activities (Skellam et al, 2013). In this regard, auroramycin, a polyene macrolactam, was produced by a strain of Streptomyces roseosporous with anti-MRSA and antifungal properties (Yeo et al, 2020). Additionally, Arai et al (2017) also found that an isomer of micromonolactam, isomicromonolactam, could be used as an enhancer of neural stem cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the biosynthetic capacity of the CH strain, we selected four heterologous polyketide BGCs producing antibiotic and anti-fungal polyketides, including the well-studied actinorhodin [44] and erythromycin [45], together with the recently discovered auroramycin [46,47] and bipentaromycin [48] (Fig. 3).…”
Section: Heterologous Expression Of Exogenous Bgcsmentioning
confidence: 99%
“…Some of the most recent works are CRISPR/Cas-based strategies for unearthing the hidden chemical space [ 147 ]. Using a CRISPR-Cas9 gene cluster activation strategy, a unique macrolactam glycosylated by two aminosugars, auroramycin ( Figure 19 ), was isolated [ 148 , 149 ]. A transcription factor decoy strategy for targeted activation of large BGCs was reported [ 150 ].…”
Section: Molecular Biologymentioning
confidence: 99%